Upregulation of K2P3.1 K+ Current Causes Action Potential Shortening in Patients With Chronic Atrial Fibrillation. Issue 2 (14th July 2015) - Schmidt, Constanze; Wiedmann, Felix; Voigt, Niels; Zhou, Xiao-Bo; Heijman, Jordi; Lang, Siegfried; Albert, Virginia; Kallenberger, Stefan; Ruhparwar, Arjang; Szabó, Gábor; Kallenbach, Klaus; Karck, Matthias; et al.
<x xml:space="preserve">Abstract</x> Background— Antiarrhythmic management of atrial fibrillation (AF) remains a major clinical challenge. Mechanism-based approaches to AF therapy are sought to increase effectiveness and to provide individualized patient care. K2P3.1 (TASK-1 [tandem of P domains in a weak inward-rectifying K+ channel–related acid-sensitive K+ channel-1]) 2-pore-domain K+ (K2P) channels have been implicated in action potential regulation in animal models. However, their role in the pathophysiology and treatment of paroxysmal and chronic patients with AF is unknown. Methods and Results— Right and left atrial tissue was obtained from patients with paroxysmal or chronic AF and from control subjects in sinus rhythm. Ion channel expression was analyzed by quantitative real-time polymerase chain reaction and Western blot. Membrane currents and action potentials were recorded using voltage- and current-clamp techniques. K2P3.1 subunits exhibited predominantly atrial expression, and atrial K2P3.1 transcript levels were highest among functional K2P channels. K2P3.1 mRNA and protein levels were increased in chronic AF. Enhancement of corresponding currents in the right atrium resulted in shortened action potential duration at 90% of repolarization (APD90) compared with patients in sinus rhythm. In contrast, K2P3.1 expression was not significantly affected in subjects with paroxysmal AF. Pharmacological K2P3.1 inhibition prolonged APD90 in atrial myocytes from patients with chronic AF to values observed among control subjects in sinus rhythm. Conclusions— Enhancement of atrium-selective K2P3.1 currents contributes to APD shortening in patients with chronic AF, and K2P3.1 channel inhibition reverses AF-related APD shortening. These results highlight the potential of K2P3.1 as a novel drug target for mechanism-based AF therapy.